Can measures of strain and acceleration be used to predict breast discomfort during running?. (September 2013) - Haake, Steve; Milligan, Alex; Scurr, Joanna
The aim of this study was to determine whether dynamic breast properties could be used as objective measures of discomfort in the breast during running. Relative breast motion was measured in eight women with breast sizes ranging from 32A to 34G while running on a treadmill at 10 and 14 km·h −1 wearing either no bra, an everyday bra or an encapsulated sport bra. Kinematic data was converted to dynamic strain, ε ma x, and differentiated twice to give maximum dynamic acceleration, a max . Discomfort scores from 0 to 10 (comfort to discomfort) were recorded after each test. Discomfort was found to increase with both ε ma x or a max ; additionally ε ma x and a max generally demonstrated a positive linear relationship for all participants. Discomfort score and ε ma x increased with breast size, while discomfort score and a max decreased with the use of a bra. A transition between comfort (scores between 0 and 5) and discomfort (scores between 6 and 10) was approximated on the basis of ε ma x and a max and tested against the real score given by the participants. The simple model agreed with the participants' perceptions of discomfort in 77% of cases and was 10.5 times more likely to predict the classification correctly than incorrectly. It was concluded that breast discomfort during exercise is a function of both ε ma x and a max, and strategies to decrease discomfort in the breast during exercise should aim to minimize both parameters.